Diversity Among Cyanobacterial Photosystem I Oligomers - Chen, Ming; Liu, Xuan; He, Yujie; Li, Ningning; He, Jun; Zhang, Ying (Frontiers in Microbiology, 2022)
Abstract Unraveling the oligomeric states of the photosystem I complex is essential to understanding the evolution and native mechanisms of photosynthesis. The molecular composition and functions of this complex are highly conserved among cyanobacteria, algae, and plants; however, its structure varies considerably between species. In cyanobacteria, the photosystem I complex is a trimer in most species, but monomer, dimer and tetramer arrangements with full physiological function have recently been characterized. Higher order oligomers have also been identified in some heterocyst-forming cyanobacteria and their close unicellular relatives. Given technological progress in cryo-electron microscope single particle technology, structures of PSI dimers, tetramers and some heterogeneous supercomplexes have been resolved into near atomic resolution. Recent developments in photosystem I oligomer studies have largely enriched theories on the structure and function of these photosystems.